PENGARUH GAJI DAN INSENTIF TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PBM ADHIGUNA PUTERA KABUPATEN PROBOLINGGO - Aprilia, Dina Dwi; Karnadi, Karnadi; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2022)
The research objective is to determine the effect of salary and incentives on employee performance with job satisfaction as an intervening variable at PT. PBM Adhiguna Putera, Probolinggo Regency. The sampling technique used in this study is a saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results show that salary has a positive and significant effect on job satisfaction, incentives have a positive and significant effect on job satisfaction, salary has a positive and significant effect on employee performance, incentives have a positive and significant effect on employee performance, job satisfaction has a negative but significant effect on employee performance, Salary has a negative but significant effect on employee performance through job satisfaction, incentives have a negative and insignificant effect on employee performance through job satisfaction.